Use of Yellow Fluorescent Protein Fluorescence to Track OPR3 Expression in Arabidopsis Thaliana Responses to Insect Herbivory - Body, Mélanie J.A.; Dave, Dhruveesh F.; Coffman, Clayton M.; Paret, Taylor Y.; Koo, Abraham J.; Cocroft, Reginald B.; Appel, Heidi M. (Frontiers in Plant Science, 2019)
Feeding by chewing insects induces chemical defenses in plants that are regulated by the jasmonic acid (JA) pathway. Jasmonates are usually quantified by liquid chromatography – mass spectrometry (LC-MS) analysis of precursors and products in the biosynthetic pathway or inferred from the extraction and expression of genes known to respond to elevated levels of JA. Both approaches are costly and time consuming. To address these limitations, we developed a rapid reporter for the synthesis of jasmonic acid (JA) based on the OPR3promoter:YFP-PTS1. YFP fluorescence was increased by mechanical wounding and methyl jasmonate (MeJA) treatment and by caterpillar feeding. To develop an optimal sampling time for a quantitative bioassay, OPR3promoter:YFP-PTS1 plants were sampled at 1, 2, 3, and 24 hours after treatment with 115 µM MeJA. The first increase in YFP fluorescence was detected at 2 hours and remained elevated 3 and 24 hours later; as a result, 3 hours was chosen as the sampling time for a quantitative bioassay of jasmonate response to insect attack. Feeding by Pieris rapae caterpillars induced a 1.8-fold increase in YFP fluorescence, consistent with the known induction of JA production by this insect. We also assessed the utility of this reporter in studies of plant responses to caterpillar feeding vibrations, which are known to potentiate the JA-dependent production of chemical defenses. Pretreatment with feeding vibrations increased expression of the OPR3promoter:YFP-PTS1 in response to 14 µM MeJA. Feeding vibrations did not potentiate responses at higher MeJA concentrations, suggesting that potentiating effects of prior treatments can only be detected when plants are below a response threshold to the elicitor. The expression of OPR3 does not indicate levels of specific downstream jasmonates and quantification of specific jasmonates still requires detailed analysis by LC-MS. However, OPR3 expression does provide a rapid and inexpensive way to screen large numbers of plants for the involvement of jasmonate signaling in their response to a wide variety of treatments, and to study the induction and expression of AtOPR3.